DYSMETABOLIC NEPHROPATHY: GLOBAL AND REGIONAL PREVALENCE (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Dysmetabolic nephropathy (DMN) in children is a significant and growing health concern worldwide, particularly in regions with environmental pollution and dietary imbalances. While comprehensive global prevalence data are limited, regional studies provide insight into the burden of this condition. Ukraine (Dnipropetrovsk Region): A study involving 297 children diagnosed with DMN found a higher prevalence in girls (72.6%) compared to boys (27.4%). Oxalate nephropathy was predominant, observed in 88.1% of cases. Notably, 73% of these children also had urinary tract infections, and 68.9% were diagnosed with pyelonephritis.